2020
DOI: 10.1093/rheumatology/kez639
|View full text |Cite|
|
Sign up to set email alerts
|

Percutaneous coronary intervention outcomes in patients with rheumatoid arthritis, systemic lupus erythematosus and systemic sclerosis

Abstract: Objective Patients with autoimmune rheumatic disease (AIRD) are at an increased risk of coronary artery disease. The present study sought to examine the prevalence and outcomes of AIRD patients undergoing percutaneous coronary intervention (PCI) from a national perspective. Methods All PCI-related hospitalizations recorded in the US National Inpatient Sample (2004–2014) were included, stratified into four groups: no AIRD, RA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
1
12
1
Order By: Relevance
“…Previous studies found in patients with AIRD increased post‐PCI short‐term mortality 6–8 . Our result presents a clear trend (however failed to reach statistical significance) of increased risk of long‐term mortality.…”
Section: Discussioncontrasting
confidence: 59%
See 2 more Smart Citations
“…Previous studies found in patients with AIRD increased post‐PCI short‐term mortality 6–8 . Our result presents a clear trend (however failed to reach statistical significance) of increased risk of long‐term mortality.…”
Section: Discussioncontrasting
confidence: 59%
“…This group includes autoimmune rheumatic diseases (AIRD), that is, systemic lupus erythematosus (SLE) and Rheumatoid arthritis (RA) 1,2 and inflammatory bowel diseases (IBD) 3–5 . AIRD patients comprise about 0.8%–1.4% of all patients undergoing percutaneous coronary intervention (PCI), and data regarding outcomes are conflicting 6 . A previous large cohort did not find increased rate of in‐hospital mortality, stroke and bleeding in and RA compared to the non‐AIRD population 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth to emphasize that patients with SSc have higher rate of acute coronary syndromes, but also their treatment is fraught with higher risk of complications. SSc patients undergoing percutaneous coronary interventions were more likely to exhibit in-hospital complications than patients without connective tissue disorders, with much more higher in-hospital all-cause mortality (OR 1.32, 95%CI 1.03–1.71) 16 .…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Despite previous reports of worse PCI-related outcomes with some chronic inflammatory conditions, there is limited evidence on procedural outcomes of PCI in patients with IBD. [11][12][13][14][15] we examined the prevalence of IBD, their clinic a l characteristics and in-hospital outcomes in patients undergoing PCI from a nationa lly representative sample in the United States (US).…”
Section: Introductionmentioning
confidence: 99%